EDUKASI PENGABDIAN KEPADA MASYARAKAT DALAM MENANAM KACANG PANJANG GUNA MENINGKATKAN PENGHASILAN DI DESA HILIWETO KECAMATAN GIDO KABUPATEN NIAS - Lase, Famahato Lase; Yanida Bu’ulolo; Destin Nirmala Zebua; Estian Gulo; Erika Zalukhu; Fince Putra Jaya Zalukhu; Iman Kristiani Harefa; Juli Antonius Waruwu; Restu Jaya Gulo; Jeni Firman Gea; Julasti Solia Laoli (Asosiasi Dosen Muda Indonesia, 2024)
Abstract: Skills in planting long beans to obtain results are carried out through community service activities by providing education to them. The aim of this community service research is to provide education to the public so that they are able to understand well how to plant long beans successfully, including: how to choose and prepare the location of the soil and long bean seeds, how to plant the seeds and care for and prune them, how to help eradicate pests and diseases , and how to maintain a sustainable harvest and the benefits of growing string beans. The method used is giving examples directly, the participants are the people of Hiliweto Village, Gido District, Nias Regency, North Sumatra and the education providers are Nias University students who are carrying out community service activities with the guidance of lecturers. The research results concluded that: (1) community service education is very effective in providing knowledge, attitudes and skills in planting long beans successfully; (2) The ways to plant long beans are: selecting and preparing the location of the soil and long bean seeds by digging a hole in the ground with a depth of about 2 to 3 cm, and the distance between the holes is about 20 to 30 cm, and the distance between the rows is about 60 to 80cm; (3) supporting plants by eradicating pests and diseases and maintaining sustainable harvests by selecting superior, large and good seeds and getting the benefits of planting long beans.